The conversion of cognitive interjections in classical English literature into Indonesian - Nadia Khumairo Ma'shumah; Arif Nur Syamsi; Susana Widyastuti (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
Translating interjections is notoriously challenging. Aside from their ambiguous and context-dependent meanings, they also express emotions through broadly suggestive sensations, attitudes, and states of mind. This study attempts to uncover emotional meanings embedded in cognitive interjections, the conversion strategies of cognitive interjections, and how the conversion strategies affect correspondence and equivalence. The data were interjective expressions in the classic English literature entitled